Wrestling with the Monster: Frankenstein and Organ Transplantation. Issue 6 (26th December 2018) - Trump, Eric
Abstract: In December 1967, Louis Washkansky, a grocer living in South Africa, became the first person to awaken after a heart transplant. Some accounts say that his first words were, "I am the new Frankenstein." Others claim that Christiaan Barnard, his transplant surgeon, uttered these. Much as people have long mixed up who Frankenstein is—creature or creator?—in Mary Shelley's novel, so patient and surgeon, repaired and repairer, are confused in retellings of this post‐op Frankensteinian moment. Whether Washkansky identified with Frankenstein's monster or not, he was probably feeling a bit monstrous after taking the donor heart of Denise Darvall into his chest. I know I was, over thirty years later, standing naked before a mirror and gazing at my shorn and bloated torso for the first time since a kidney transplant. My boundaries had been rearranged: a crescentic scar marked the frontier between me and not‐me .